Análisis de la atención al usuario en el Gobierno Autónomo Descentralizado Parroquial Rural de Pimocha, cantón Babahoyo, Provincia de Los Ríos - Carpio Peñafiel, Carlos Gustavo (2021)
The GADs in Ecuador are the entities that are in charge of the administration and resolution of the users of said canton, with the aim that they feel comfortable and can enjoy a legal life within said canton that is pleasant. This work presents the way in which this GAD works and presents its situation, at the same time recommending some methods so that the weaknesses that were detected in user care are corrected or taken into consideration when making decisions, for GAD authorities, in order to achieve the satisfaction of people who come to resolve any legal situation with their land, payments for basic services administered by the GAD, PARISH OF PIMOCHA.